2012
DOI: 10.1088/0026-1394/49/3/209
|View full text |Cite
|
Sign up to set email alerts
|

Self-locked operation of large He–Ne ring laser gyroscopes

Abstract: Helium–neon ring laser gyroscopes have been observed to produce a stable and useful Sagnac beat signal while operating with multiple longitudinal modes through a mode-locking mechanism. The parameter space pertaining to stable operation with respect to gas pressure and intra-cavity power has been explored experimentally. Two regions of stability have been identified. The stability of large ring lasers operating with mode-locking has been characterized. Mode-locked operation presents no statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This technique is very easy to be implemented, but multi-mode operation can produce a decrease of sensitivity. This technique was successfully applied to the G0 ring operating in Canterbury (NZ) [11], which had an excellent Sagnac signal also in presence of multimode operation. It was however observed that the spectrum of the secondary modes were not stable.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…This technique is very easy to be implemented, but multi-mode operation can produce a decrease of sensitivity. This technique was successfully applied to the G0 ring operating in Canterbury (NZ) [11], which had an excellent Sagnac signal also in presence of multimode operation. It was however observed that the spectrum of the secondary modes were not stable.…”
Section: Experimental Set-upmentioning
confidence: 99%